2004
DOI: 10.1038/sj.leu.2403542
|View full text |Cite
|
Sign up to set email alerts
|

Multipotent neural precursors express neural and hematopoietic factors, and enhance ex vivo expansion of cord blood CD34+ cells, colony forming units and NOD/SCID-repopulating cells in contact and noncontact cultures

Abstract: In view of the possible crosstalks between hematopoiesis and neuropoiesis, we evaluated two microenvironments, murine neonatal neural cell line C17.2 and primary embryonic aortagonad-mesonephros (AGM) stromal cells, on the ex vivo expansion of CD34 þ cells from human cord blood. In a contact culture system, C17.2 or AGM cells significantly enhanced the expansion of CD34 þ cells to a panel of early and committed hematopoietic progenitor cells. In a noncontact transwell system, pre-established C17.2 cells signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…Colonies were scored in a blinded manner. Colony‐forming unit‐megakaryocytes (CFU‐MK) were assayed using the plasma clot system as described previously [33, 34]. CFU‐MK was identified as a cluster of three or more strongly stained CD61‐FITC (Dako) positive cells examined by fluorescence microscopy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Colonies were scored in a blinded manner. Colony‐forming unit‐megakaryocytes (CFU‐MK) were assayed using the plasma clot system as described previously [33, 34]. CFU‐MK was identified as a cluster of three or more strongly stained CD61‐FITC (Dako) positive cells examined by fluorescence microscopy.…”
Section: Methodsmentioning
confidence: 99%
“…In each independent cord blood experiment ( n = 16), cells expanded in the presence or absence of serotonin were infused into sex‐ and age‐matched mice (progenies of 3 × 10 4 CD34 + cells at day 0 per mouse). To prevent the loss of data due to animal mortality, two mice were assigned to each treatment group, and the engraftment parameters averaged as a single datum for analysis, as described previously [33, 34]. These animals were sacrificed 6 weeks post‐transplantation.…”
Section: Methodsmentioning
confidence: 99%
“…A report by Jang et al showed that MSC derived from human umbilical cord, human placenta, and lung could support ex vivo expansion of committed HPCs collected from the UCB in the presence of recombinant cytokines [7]. Li et al reported that murine neonatal neural cell line C17.2 significantly increased the expansion of total nucleated cells, CD341 cells, and multilineage colony forming cells at a noncontact condition [8]. Moreover, porcine microvascular endothelial cell [9], human yolk sac-derived endothelial cells (hYSECs) [10], umbilical vein endothelial cells (HUVEC) [11], osteoblasts [12], and extracellular matrix [13] have also been reported to play a significant role in HSPCs expansion.…”
Section: Expansion Of Hspcs By Coculturing With Stromal Feeder Cell Lmentioning
confidence: 99%
“…Enriched CD34 + cells or expanded cells at 3 · 10 3 /ml were seeded in triplicate. Colonies were scored after culturing for 14 d. Megakaryocyte colony forming units (CFU-MK) were assayed using the plasma clot system as described previously (Li et al, 2005(Li et al, , 2006. CFU-MK was identified as a cluster of three or more strongly stained CD61-FITC (Dako) positive cells examined by fluorescence microscopy.…”
Section: Colony-forming Unit Assaymentioning
confidence: 99%
“…CD34 + cells were enriched using the VarioMACS Isolation Kit (Miltenyi Biotec Inc., Gladbach, Germany) as described previously (Li et al, 2005(Li et al, , 2006 and respective isotype controls for 20 min. All antibodies and cytometric reagents were purchased from Becton DickinsonPharmingen (BD, San Jose, CA, USA), unless specified otherwise.…”
Section: Purification Of Narcissus Tazetta Lectins Ntlmentioning
confidence: 99%